Terorisme di Aceh: Studi Analisis Sosial-Budaya Tentang Penolakan Masyarakat Aceh Terhadap Gerakan Radikal Tandhim Al Qaidah Serambi Makkah - Apridar, Apridar; Subhani, Subhani; Chaidar, Al (Universitas Malikussaleh, 2014)
Issues raised in this study are: what and how the terrorist movement could emerge in Aceh which are known to have a different Islamic characteristics? This study will examine how the transformation of ideological belief within the Acehnese to accept and/or to reject the radical Islamic movements that have been entered and began to spread in Aceh. This study will focus on the analysis of the ideology of